Single-probe Mass Spectrometry as a Bioanalytical Tool for Quantitative Single Cell Analysis: From Cell Lines to Patients - Standke, Shawna (My University, 2019)
Cellular processes are traditionally characterized using bulk analysis. However, cell population averaging techniques are unable to accurately characterize these processes as each cell is extremely heterogeneous and can have different properties based on cell morphology, size, or growth phase, etc. Additionally, cell population averaging contains extensive sample preparation, which could alter cellular metabolites. Cells are sensitive to environmental perturbation (e.g. centrifugation, trypsinization, temperature fluctuation, etc.), so the sample preparation needed for bulk population analysis may skew results. With advancements in instrumentation and bioanalytical tools, single cell analysis techniques have been increasingly characterized in the past decade. Single cell mass spectrometry is a popular method for single cell analysis since high resolution mass spectrometers are extremely sensitive and can extract information for a broad range of compounds using only the volume of a single cell (i.e. a few picoliters of solution). Ambient mass spectrometry techniques have been utilized for single cell analysis since they require little to no sample preparation and can give more representative results about each individual cell in a near-native environment. Furthermore, live-video single cell mass spectrometry techniques have been developed to capture real-time analysis of cellular compounds from individual cells. In this work, the Single-probe mass spectrometry method has been increasingly characterized and developed for use on a variety of cell types. The Single-probe is a microscale sampling device that couples with a mass spectrometer for the real-time analysis of live, single cells under ambient conditions. First, the Single-probe mass spectrometry technique was used to detect drug compounds from individual cells (results not published). Then, a setup was created to allow for the analysis of suspension cells in solution to enable the testing of a variety of cell types from complex solutions. Next, the Single-probe mass spectrometry method was adapted for the first-time quantification of mammalian cancer cell lines for adherent cells. The quantitative single cell analysis technique was then used to explore drug metabolism on the single-cell level. Finally, cells derived from the urine of bladder cancer patients was tested, and we report the first quantification of anti-cancer compounds from single cells that were collected non-invasively.
Keywords: Chemistry, Analytical.; Single Cell; Quantification; Mass Spectrometry